MODEL MANAJEMEN MUTU BERBASIS KEPATUHAN REGULASI UNTUK PENINGKATAN KINERJA PELAYANAN DI TERMINAL UNTUK KEPENTINGAN SENDIRI (TUKS) WILAYAH KERJA KSOP PEKANBARU - Gradina Nur Fauziah; Fery Kurniawan; Andi Nurhidayanti (JURNAL SAINS DAN TEKNOLOGI MARITIM, 2026)
The purpose of this conceptual study is to formulate a quality management model for port services at Terminals for Own Interest (TUKS), focusing on regulatory compliance aspects, based on an in-depth analysis of the Cooperation Agreements (PKS) between the Port Authority and Harbour Master’s Office (KSOP) Class II/III Pekanbaru and various TUKS operators. TUKS is a crucial element in the national logistics chain, whose operations are highly dependent on the legal framework stipulated in the PKS, covering aspects of maritime safety, security, and environmental protection (Angkasa & Darmawan, 2024). The method used is qualitative document analysis (PKS) to identify primary quality variables: Regulatory Compliance and Partnership Sustainability. The analysis results show that the PKS serves as a quality instrument that obligates TUKS operators to meet minimum operational standards. The proposed model is the "Compliance-Driven Quality Management (CDQM)" which places the fulfillment of rights and obligations within the PKS as the primary indicator of quality performance. CDQM emphasizes (1) Requirement Alignment (PKS, Laws, PM), (2) Quality Processes based on PKS Milestones, and (3) Quality Review Mechanisms (Addendum/Dispute Resolution Clauses) (Hidayat et al., 2025). The implementation of this model is expected to improve TUKS operational efficiency and ensure maritime safety and security in port waters.